True and Fair View of Derivative Instruments in Hedge Accounting Model Under IFRS 9 - Dunal, Patryk; Andrzejewski, Mariusz; Ożga, Paweł (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
Accounting of derivative instruments under International Accounting Standard 39 (IAS 39) were criticised due to the complexity and mismatch to business reality. Superseding IAS 39 with International Financial Reporting Standard 9 (IFRS 9) was aimed to simplify hedge accounting principles and contribute to the wider use of this model, and, on the other hand, to eliminate the imperfections of the previous standard and improve the quality of information on derivative instruments disclosed in the financial statements. IFRS 9 introduced a number of changes in the accounting of derivative instruments and therefore it seems reasonable to discuss their consequences and the impact on the reliability and credibility of information disclosed on derivatives. This is extremely important because derivatives are associated with a significant risk and often their improper use led to significant financial problems or even bankruptcy of enterprises and financial institutions. The purpose of this article is to present the most important changes in accounting for derivatives implemented in IFRS 9 and to analyze their impact on financial statements, i.e. true and fair reflection of economic effects of using derivatives.